The recognizable face of fear: Domestication and redemption of the animal monster in The Exorcist - Marcia Heloisa Amarante Gonçalves (Gragoatá, 2013)
This article analyses the function of animal traits in the transformation from human to monster in the movie “The Exorcist”, based on the homonymous best-seller by William Peter Blatty. Released in 1973, it remains one of the most disturbing accomplishments of Horror cinema and stands as a seminal work of the demonic movie subgenre. The Horror narrative describes a journey in which the animal, by virtue of its ubiquitous presence in our lives, frequently acts as a psychopomp. Although the depiction of animality as a mark of villainy has been detrimental to our perception of some animals, it has nevertheless contributed to an ongoing reflection about the human-animal relationship. Horror narratives remain the main locus of animality in works of fiction, for their unrivalled ability to gather archetypical representations and   to invite us to experience a vicarious confrontation with our own repressed fears. The article proposes a reflection on animality as a path to reintegration of the Self, defending the endurance of animal monsters in the Horror genre.